Pharmacoeconomic Analysis - The Way to Optimization of Using the Health Budget - Tetiana Nehoda (Journal of Global Pharma Technology, 2020)
Reforming the drug supply system requires the introduction of modern scientific approaches to quality management of pharmacotherapy, the main principle of which is the individual selection of the drug taking into account its effectiveness and safety. Introduction: To analyze the literature on the need and feasibility of using pharmacoeconomic methods to provide medicines. Materials and methods: The basis for research is the methods of pharmacoeconomics. Results: The analysis of the data of literature sources was carried out and the necessity of using pharmacoeconomic methods in the field of health care was determined. Conclusions: As a result of the review, it was determined that pharmacoeconomic analysis is an effective method that facilitates the adoption of optimal decisions in the field of drug supply. Keywords: Arterial hypertension; Health care, Antihypertensive drugs; Form system.